Pendampingan Tata Kelola Badan Usaha Milik Desa ( BUMDes) di Desa Muaro Sentajo Kecamatan Sentajo Raya Kabupaten Kuantan Singingi - Rosmayani Rosmayani; Annisa Mardatillah (PELANTAR PRESS, 2022)
Village-owned enterprises provide many benefits for village communities to be able to improve the village economy. One of the goals established by BUMDes is to improve the village economy. One of the goals of establishing BUMDes is to eradicate poverty in the village community and empower the potential of the village. This community service activity aims to assist the management of BUMDes in the village of Muaro Sentajo, Sentajo Raya District, Kuantan Singingi Regency. The results of the outreach activities for mentoring the governance of BUMDes can be arranged planning work programs based on the results of discussions between the PKM team, village officials, BUMDes managers and the local community. The mentoring for BUMDes governance provides solutions to problems faced by other things related to all human resources for BUMDes managers, namely providing technical guidance, management of existing BUMDes businesses but not yet optimal, (Savings and Loans, BRI Link, Saprodi Fertilizer, Agricultural Equipment and Agricultural Medicine).